Multi-criteria decision aid : evaluation and comparison of main techniques/tools - Tereso, Anabela Pereira (2010)
Good decision making is increasingly more important to organizations. This work presents a review of the literature in multicriteria decision aid with a reference to the main techniques available in the area. We also present a research on the software tools available in this field. These software tools were then characterized and classified and their main characteristics summarized in the present work. This work is part of a project that has as final goal to implement a software tool using AHP to help on the selection of the right multicriteria decision aid software.